1996
DOI: 10.1123/apaq.13.3.302
|View full text |Cite
|
Sign up to set email alerts
|

Teaching across the Curriculum: Language-Enriched Physical Education for Preschool Children

Abstract: Children age 4 to 6 years from special education (n = 26), Head Start (n = 35), and typical preschool classes (n = 11) were assigned to a physical activity intervention or a language-enriched physical activity intervention. Language and motor skill performances were measured before, immediately following, and 3 months following the 24-session, 8-week intervention. Results illustrated that language instruction can be added to physical education lessons without requiring additional instructional time and, more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 5 publications
3
38
1
3
Order By: Relevance
“…Kelly et al 9 e Connor-Kuntz & Dummer 10 verificaram aprimoramento de habilidades motoras globais em pré-escolares após a intervenção motora. As habilidades motoras finas também podem ser significativamente aprimoradas em pré-escolares com atraso no desenvolvimento 11 .…”
Section: Campos Et Alunclassified
See 1 more Smart Citation
“…Kelly et al 9 e Connor-Kuntz & Dummer 10 verificaram aprimoramento de habilidades motoras globais em pré-escolares após a intervenção motora. As habilidades motoras finas também podem ser significativamente aprimoradas em pré-escolares com atraso no desenvolvimento 11 .…”
Section: Campos Et Alunclassified
“…Os relatos encontrados na literatura concentram-se no efeito da intervenção realizada precocemente, possivelmente porque se verifica que, quanto menor a idade das crianças, maior é o efeito positivo da estimulação [8][9][10][11] . Porém, poucos estudos esclarecem se crianças que não tiveram oportunidade de estabelecer desenvolvimento psicomotor adequado no início da infância podem ser estimuladas posteriormente ou estão fadadas a conviver com dificuldades.…”
Section: Campos Et Alunclassified
“…Prime opportunities to provide key experiences for motor skill improvement are missed. Studies have contributed evidence that fundamental motor skills can be strengthened and improved in young children if structured, quality instruction is furnished (Connor-Kuntz and Dummer, 1996;Pica, 1995;Zittel and McCubbin, 1996). Research also indicated active intervention, using developmentally appropriate materials and activities, successfully promoted fundamental gross motor development in at-risk preschoolers (Goodway and Rudisill, 1996;Payne and Rink, 1997).…”
Section: Discussionmentioning
confidence: 95%
“…Researchers have reported that enhancement of cognitive skills, social skills, and perceived competence correlates with competency in fundamental movements skills in preschool children (Connor-Kuntz and Dummer, 1996;Goodway and Rudisill, 1996). Deficits in fundamental movement may result in difficulties in the classroom and on the playground, as well as a lower self-concept (Gallahue and Ozmun, 1998).…”
Section: R J Woodardmentioning
confidence: 96%
“…Several studies have shown important and positive results from motor skill intervention during early childhood (Connor -Kuntz & Dummer, 1996;Goodway & Branta, 2003;Goodway, Crowe, & Ward, 2003;Lemos, Avigo, & Barela, 2012;Marshall & Bouffard, 1997;Palma, Camargo, & Pontes, 2012;Rodrigues, Avigo, Leite, Bussolin, & Barela, 2013;Valentini & Rudisill, 2004a, 2004b. investigated two groups of American kindergarten children identified as being at risk for motor development delay.…”
Section: Introductionmentioning
confidence: 99%